Magnetic polyester bis-MPA dendron nanohybrid demulsifier can effectively break water-in-crude oil emulsions - Umar, A.A. (Elsevier Editora Ltda, 2020)
Crude oil is normally produced in the form of a water-in-oil (W/O) emulsion. One of the major challenges during crude oil exploration is the high viscosity of crude oil produced due to the formation of stable emulsions. This affects the overall cost of crude oil transport, promotes salt deposition in crude oil refining equipment, and ultimately poison catalysts during the crude oil refining process. To improve the market value of crude oil, finding sustainable strategies to tackle these impending problems is crucial. This present study reports a new Fe3O4-based nanohybrid demulsifier, indexed as PEDHA-Fe3O4. The PEDHA-Fe3O4 nanohybrid demulsifier was successfully synthesized through the covalent functionalization of magnetite (Fe3O4) nanoparticles with Polyester bis-MPA dendron, 2-hydroxyl, 1-azide dendrimer. Through vibrating sample magnetometer analysis, it was found that the PEDHA-Fe3O4 nanohybrid demulsifier exhibited superparamagnetic behavior with an optimum saturation magnetization (Ms) of 63.913 emu/g and 33.559 emu/g when functionalized with â¼25 mg and 50 mg respectively. Using an attenuated total reflectance (ATR)-FTIR analysis of PEDHA-Fe3O4 nanohybrid demulsifier, mid-IR-absorption peaks were observed at â¼418 FTIR absorption bands were 6 cm-1 and 4134 cm-1 for 25 and 50 mg loadings respectively. According to quantum chemical-based FTIR analysis of PEDHA-Fe3O4 nanohybrid demulsifier, the IR-absorption can be assigned to C-H-O covalent linkages between the PEDHA dendrimer and Fe3O4 nanoparticle. At 15 mg/L dosage, the PEDHA-Fe3O4 nanohybrid demulsifier recorded 71.2 efficiency in breaking water-in-crude oil emulsion accrued to the reduction in the interfacial tension (IFT) values between oil and water from 2.67 to 0.77 mN/m. The water removal percentage by the PEDHA-Fe3O4 nanohybrid demulsifier was â¼78.13 after 50 h. Therefore, PEDHA-Fe3O4 nanohybrid demulsifier performed better than the commercial DTG-62 (Ethoxylated or Epoxidized PAG-based demulsifiers) which recorded â¼2.02 water removal. Cross-polarized microscopy (CPM) was used to visualize the image of the water removal by the PEDHA-Fe3O4 nanohybrid demulsifier. Accordingly, differential light scanning (Turbiscan) analysis supported the high performances of the PEDHA-Fe3O4 nanohybrid demulsifier in breaking of W/O emulsions. In general, these results offer new opportunities in the oil and gas facilities to explore interfacial phenomena as it applies to crude oil treatment particularly for enhanced transport to meet market and refinery specifications. Â© 2020 The Author(s).